A dyrosaurid from the Paleocene of Senegal. (3rd December 2018) - Martin, Jeremy E.; Sarr, Raphaël; Hautier, Lionel
Abstract: We describe a partial dyrosaurid skeleton recently prepared out of a limestone block discovered in the 1930s from Danian strata along the Atlantic coast of Senegal. The specimen, from a single individual, comprises nicely preserved elements of the appendicular and axial skeleton from the abdominal and sacral region, which enables us to refine our knowledge on some postcranial characteristics of the Dyrosauridae. Although Dyrosauridae are abundant in early Eocene deposits of North Africa, the present discovery in the Danian of Senegal fills a patchier record early after the K/Pg boundary and provides an important comparative data point with the few other Danian dyrosaurid records such as Atlantosuchus from nearby Morocco or Guarinisuchus and Hyposaurus from Brazil and the USA, respectively.